The Response by the Norwegian Aluminium Industry to Changing Market Structure - Kjersti-Gro Lindquist (Statistics Norway, Research Department, 1998)
This paper analyses how changes in market structure have affected the margins (measured by the Lerner index) of Norwegian aluminium plants. Instead of showing the expected negative trend, due to increased competition internationally, the margins are found to move procyclically around a constant that significantly exceeds zero. Three explanations for this stability in the levels of the margins are identified; a better exploitation of scale economies, increased productivity and product specialisation which allows Norwegian producer prices to increase more rapidly than the international reference price.
Keywords: C23; D21; D43; L61; 330; Lerner index; Translog cost function; Aluminium industry; Differentiated products